HARMONIZING TRADITIONAL VALUES IN MODERN EDUCATION - Fitria Hanaris; Ach. Shobri; Nasiba Mirzayeva Bakhtiyar Kizi (LP2M Institut Agama Islam Al-Khiarat Pamekasan, 2023)
This study aims to explore the integration of traditional principles in the curriculum of Madrasah Ibtidaiyah Negeri (MIN) 2 Pamekasan. In order to achieve this goal, this research utilizes a qualitative approach with a case study type. Data collection techniques involve a series of procedures that include interviews, observations, and documentation. The results of this study make a significant contribution in designing a future hybrid education model. This model is rooted in traditional values, yet remains relevant to the demands of modern times. Thus, this research proves that modern education and traditional values can go hand in hand. This allows the younger generation to understand and appreciate their cultural heritage, while remaining prepared for the challenges of the future. This research is expected to provide new and valuable insights for educational practitioners and researchers in the same field. As such, this study has the potential to enrich academic literature and educational practice.